PENGEMBANGAN MATERI SELF CONTROL SISWA KELAS XI AKUTANSI 2 SMK MUHAMMADIYAH 2 PEKANBARU T.P. 2015/2016 - Fitri Arizka; Raja Arlizon; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :One of the efforts made in creating a better self control and positif. By increasing the self control to not be involved in matters bad affecting and self harm so as todevelop themselves optimally with positive things. The Refore, researchers found it necessary to develop amaterial about the motivation of the organization which is expected to be used bythe teacher's guidance and counselling to be given to their students. This material was compiled using the method of research and development (R&D). The purpose of thisresearch is 1) Compile the material to the appropriate self control for students of class XI Accounting 2 SMK Muhammadiyah 2 Pekanbaru. 2) To find out the quality of the self control material produced. This material is validated by the supervising lecturer I, supervising lecturer II, teacher of guidance and counseling in the school and 42 Students class XIAccounting 2 SMK Muhammadiyah 2 pekanbaru. This materials are gived to the students with the allocation 4 times (4 x 45 '). This material consists of the meaning of self control, the purpose of self control, types of self control, function of self control, factors that affect the self control, strategy of self control and the benefits of exercise self control for thestudents. Research results from the development of this material shows the quality of the material produced is in the category of "Very Good", with the acquisition of score foroverall assessment of aspects of 4,42.Keywords: Development of guidance counseling materials, self control student